Impact of service guarantee on empowerment and employee motivation in four and five star hotels in Malaysia - Mohd Shahril, Aslinda; Abdul Aziz, Yuhanis; Othman, Mohhidin; Bojei, Jamil (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This study empirically investigates the relationship between service guarantee and employee motivation in four and five star hotels in Malaysia. The analysis reported useful findings which provide further insights in service guarantee domain. Empirical evidence showed that service guarantee has no positive relationship with empowerment but it has significant impact to employee motivation. Thus, hotel industry must make employee motivation a high priority. Findings of the study will provide useful insights on the importance of service guarantee implementation in order for hotel industry to improve service quality and enhance employees’ performance.